2018
DOI: 10.1016/j.cell.2018.03.060
|View full text |Cite
|
Sign up to set email alerts
|

A Lignin Molecular Brace Controls Precision Processing of Cell Walls Critical for Surface Integrity in Arabidopsis

Abstract: The cell wall, a defining feature of plants, provides a rigid structure critical for bonding cells together. To overcome this physical constraint, plants must process cell wall linkages during growth and development. However, little is known about the mechanism guiding cell-cell detachment and cell wall remodeling. Here, we identify two neighboring cell types in Arabidopsis that coordinate their activities to control cell wall processing, thereby ensuring precise abscission to discard organs. One cell type pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
164
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(179 citation statements)
references
References 77 publications
8
164
5
2
Order By: Relevance
“…Casparian strip membrane domain proteins are specifically expressed in the root endodermis, where they direct lignin deposition and therefore CS formation by scaffolding lignin polymerization enzymes such as PER64 (Lee et al , ). Previous studies and ours reveal that 34 Arabidopsis CASPLs are expressed in tissue‐ and condition‐specific manners, for example, in the abscission zone (CASPL1D1, CASPL1D2, CASPL4B1, CASPL4D1, and CASPL4D2; Roppolo et al , ; Lee et al , ) and the anther wall (CASPL1F1; Roppolo et al , ), and in response to cold stress (CASPL4C1; Yang et al , ) and biotic stress (CASPL1D1 and CASPL4D1; in this study). When ectopically expressed in the endodermis, many CASPLs behaved like CASPs, accumulating at the CS membrane domain (Roppolo et al , ).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Casparian strip membrane domain proteins are specifically expressed in the root endodermis, where they direct lignin deposition and therefore CS formation by scaffolding lignin polymerization enzymes such as PER64 (Lee et al , ). Previous studies and ours reveal that 34 Arabidopsis CASPLs are expressed in tissue‐ and condition‐specific manners, for example, in the abscission zone (CASPL1D1, CASPL1D2, CASPL4B1, CASPL4D1, and CASPL4D2; Roppolo et al , ; Lee et al , ) and the anther wall (CASPL1F1; Roppolo et al , ), and in response to cold stress (CASPL4C1; Yang et al , ) and biotic stress (CASPL1D1 and CASPL4D1; in this study). When ectopically expressed in the endodermis, many CASPLs behaved like CASPs, accumulating at the CS membrane domain (Roppolo et al , ).…”
Section: Discussionmentioning
confidence: 65%
“…Lignin would provide rigidity and hydrophobicity to CS and CSL, which then renders these structures suitable for sealing the extracellular space of juxtaposed cells. The role of lignin as a mechanical barrier has additionally been demonstrated in a recent study, in which lignin accumulated in secession cells of the abscission zone and blocked the diffusion of cell wall enzymes for precise organ separation (Lee et al , ). Lignin polymerization occurs via monolignol oxidation, which implicate NADPH oxidases or respiratory burst oxidase homologs (RBOHs) for reactive oxygen species (ROS) production (Kärkönen & Koutaniemi, ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…When looking at our understanding of endogenous enzymes involved in plant cell separation, significant recent advances have come from analysis of abscission (Lee et al , ; Lee, ). This has revealed a syncopated exchange of local signals (reactive oxygen‐based) between cells, leading to the formation of localized secondary cell wall synthesis, which prepares the future break point for exposure.…”
Section: Improving Mesophyll Conductancementioning
confidence: 99%
“…Genetic analysis of RBOHF function by characterization of rbohF mutants revealed that RBOHF together with RBOHD functions in ROS-dependent abscisic acid (ABA) signaling in guard cells and both are required for accumulation of reactive oxygen intermediates in plant defense responses (Torres et al, 2002;Kwak et al, 2003;Chaouch et al, 2012;Chater et al, 2015;Sierla et al, 2016;Qi et al, 2018). Moreover, it has been reported that both NADPH oxidases also function together in positively modulating ABA-mediated inhibition of root growth and in triggering organ abscission (Jiao et al, 2013;Lee et al, 2018). In addition, genetic screens for mutants impaired in the formation of the Casparian strip in roots identified rbohF mutants exhibiting delayed formation of this paracellular diffusion barrier (Lee et al, 2013).…”
Section: Introductionmentioning
confidence: 99%